Effect of laminar and turbulent flow through a curved channel with a rectangle section by using baffles in cement industry - Muhsin Al-Juhaishi, Lafta Flayih (2021)
The curved channel is commonly utilized in journal bearings of cement mill, raw mill, kilns, and high voltage engineered induction motors. The present investigation studied the improvement of heat transfer through the arched flow channel equipped with horseshoe baffles numerically and practically. The impacts of various parameters of baffles which is the attack angle (α  45˚, 60˚, and 90˚), and the number of baffles (NB=9 baffles and 13 baffles) are inspected. Water was chosen as coolant fluid for the laminar and turbulent flow domain region. A standard k-